Pengembangan media video animasi bermuatan karakter tanggung jawab pada materi nilai-nilai pancasila di sekolah dasar - Laela Nur Fauziah; Syarip Hidayat; Asep Nuryadin (IKIP Siliwangi, 2024)
Abstract This research is motivated by the low innovation of Civics learning media so that the essence of learning media is not maximized, as seen from the lack of knowledge and the provision of the character of responsibility to be based on Pancasila values ​​for students. So that from these problems, the author seeks to develop animated video media with the character of responsibility on the material of Pancasila values ​​in elementary schools. This learning media was developed using the Research and Development (R&D) method with the ADDIE model. Data collection techniques in this study included observation, interviews, document analysis, expert validation questionnaires, and student response questionnaires. The results of the validation for experts obtained an average rating of 94% from material experts in the very appropriate category, 92% from media experts in the very feasible category, and 96% from pedagogic experts in the very feasible category. Based on this, the developed learning media meets the requirements for use in learning activities. This is evidenced by the results of students' suspension of learning media in the trials of phases I and II obtaining results of 92.53% and 95.14% with very good criteria. Based on the results of expert validation and student response questionnaires, it can be concluded that animated video media with characters responsible for material Pancasila values ​​in elementary schools is appropriate for use in learning activities. Keywords: Learning Media Development, Animation Video, Responsible Character Abstrak Penelitian ini dilatarbelakangi oleh rendahnya inovasi media pembelajaran PPKn sehingga penyampaian esensi media pembelajaran belum maksimal, terlihat dari rendahnya pengetahuan dan penanaman karakter tanggung jawab berlandaskan nilai-nilai pancasila pada peserta didik. Sehingga dari permasalahan tersebut, penulis berupaya untuk mengembangkan media video animasi bermuatan karakter tanggung jawab pada materi nilai-nilai pancasila di Sekolah Dasar. Media pembelajaran ini dikembangkan menggunakan metode Research and Depelopment (R&D) dengan model ADDIE. Teknik pengumpulan data dalam penelitian ini meliputi observasi, wawancara, analisis dokumen, angket validasi ahli, dan angket respon peserta didik. Hasil validasi kepada para ahli mendapat rata-rata penilaian 94% dari ahli materi dengan kategori sangat layak, 92% dari ahli media dengan kategori sangat layak, dan 96% dari ahli pedagogik dengan kategori sangat layak. Berdasarkan hal ini, media pembelajaran yang dikembangkan sudah memenuhi syarat untuk digunakan dalam kegiatan pembelajaran. Hal ini dibuktikan berdasarkan hasil angket respon peserta didik terhadap media pembelajaran pada uji coba tahap I dan II mendapatkan hasil 92.53% dan 95.14% dengan kriteria sangat baik. Berdasarkan hasil validasi ahli dan angket respon peserta didik, maka dapat disimpulkan bahwa media video animasi bermuatan karakter tanggung jawab pada materi nilai-nilai pancasila di Sekolah Dasar layak digunakan dalam kegiatan pembelajaran. Kata Kunci: Pengembangan Media Pembelajaran, Video Animasi, Karakter Tanggung Jawab